Substrate Binding and Active Site Residues in RNases E and G: ROLE OF THE 5′-SENSOR - Garrey, Stephen M. (American Society for Biochemistry and Molecular Biology, 2009)
The paralogous endoribonucleases, RNase E and RNase G, play major roles in intracellular RNA metabolism in Escherichia coli and related organisms. To assay the relative importance of the principal RNA binding sites identified by crystallographic analysis, we introduced mutations into the 5′-sensor, the S1 domain, and the Mg(+2)/Mn(+2) binding sites. The effect of such mutations has been measured by assays of activity on several substrates as well as by an assay of RNA binding. RNase E R169Q and the equivalent mutation in RNase G (R171Q) exhibit the strongest reductions in both activity (the k(cat) decrease ∼40- to 100-fold) and RNA binding consistent with a key role for the 5′-sensor. Our analysis also supports a model in which the binding of substrate results in an increase in catalytic efficiency. Although the phosphate sensor plays a key role in vitro, it is unexpectedly dispensable in vivo. A strain expressing only RNase E R169Q as the sole source of RNase E activity is viable, exhibits a modest reduction in doubling time and colony size, and accumulates immature 5 S rRNA. Our results point to the importance of alternative RNA binding sites in RNase E and to alternative pathways of RNA recognition.